A contribuição da empresa focal no desenvolvimento de competências interorganizacionais de uma cadeia de suprimentos na indústria automotiva - Conceição, Maurício Folli (2013)
The study of strategies adopted by companies in the search for competitive advantage has been the focus of several pieces of work in the area of administration having the theme organizational competences as one of the basis for these studies. Due to the existing competition in the market, companies have been acting along with their suppliers and customers upon the identification of forms of generation of competitive advantage, that is, attempting to obtain gain in competitive advantage through interorganizational relationships. Bearing this new context in mind, authors have discussed a new approach to competences, the interorganizational competences, those which are stemmed from the relationships among companies and that generate gain to all the parties involved. Aiming at contributing to the theme interorganizational competences, an applied research has been carried out presenting an exploratory qualitative focus through a single case study of a supply chain in the automotive segment. The research aimed at identifying how the focal company, the one that is between the supplier and the customer, can contribute to the development of competences in all its supply chain. The choice for the automotive sector has been made taking into account that this is a consolidated market which also presents a high degree of competition among its players. In order to lay the foundation of this research, there has been a bibliographical review about supply chain, forms of interorganizational relationships and their key processes as well as organizational and interorganizational competences. As a result of the research, there has been the identification of a conceptual structure of development of interorganizational competences, the three existing interorganizational competences in the supply chain, the relationship among these competences and forms of contribution on the part of the focal company in the development of these competences. In addition to this, the research has enabled the proposition of a concept for the theme interorganizational competences.